IMPLEMENTASI PENDEKATAN TARL UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK SMP PADA MATA PELAJARAN IPA - Risnawanti, Virna Dwi; Supardi, Zainul Arifin Imam; Alima, Suci (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The most important part of learning is learning outcomes. The learning outcomes of each individual are influenced by the learning process of the learners. Three factors that influence student learning include internal, external, and learning approach factors. In connection with this, the author is interested in conducting research in the form of classroom action research by applying teaching at the right level (TaRL) approach. Teaching at the right level (TaRL) is a learner-oriented approach, so that the implementation of learning is carried out according to the ability of students. This research was conducted in two cycles, where each cycle consisted of four stages, including planning, implementation, observation, and reflection. The research subjects were 34 students in class VIIIB SMP Negeri 26 Surabaya, with a research period of 3 months. The research instrument consists of an assessment of student learning outcomes, which are analyzed using percentage techniques. The results showed that the percentage of students' learning outcomes always increased in each cycle, so it can be concluded that the research conducted by the author produced better learning outcomes when the teacher implemented the TaRL approach in the classroom learning process.